(untitled) - Bedient, Philip B. (Englewood Cliffs, 1994)
It provides a working knowledge of methods that have been developed to predict rates of flow and directions of movement in ground water aquifer systems along with coverage of well mechanics and a review of standard aquifer tests for determining hydraulic conductivity in the field.
Keywords: Ground water,Ground water; Pollution,Quality,Management